Herpes in Pregnancy. Issue 6 (1994) - Cook, Curtis R.; Gall, Stanley A.
Abstract : The management of genital herpesvirus infections in pregnancy has seen many changes over the past decade as we have continued to learn more about the epidemiology of the disease. This article reviews these changes and highlights ongoing controversies. Clinical management schemes are proposed based upon this most recent information.